Identifying settlements on the SIR-B images of Rimbobujang and the surrounding areas, Sumatra, Indonesia - Sutanto Sutanto (Indonesian Journal of Geography, 1988)
The use of remote sensing techniques is indispensable for Indonesia due to the large size of its territory, most of which is of difficult access and of little known regional potential. Some areas are covered by clouds almost all the year round so that remote sensing systems using visibilities up to the thermal portion of the electromagnetic spectrum fail to record them. There is no other way but to apply the microwave energy for such areas, the passive as well as the active one.This paper deals with the data extraction from Sir-B image of Rimbobujang area and its surroundings, in Sumatra, Indonesia, with special reference to the identification of settlements. It is a result of image interpretation followed by a three-days fieldchech in the study area. Comparison is also made with SPOT and La.ndsat MSS images.SIR-B image proves to be a reasonably good tool to identify rural settlement in an open area, especially for that with high density of houses. Its use to identify towns and cities is more recommended.